If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 7 = 13 + 2x Reorder the terms: 7 + 7x = 13 + 2x Solving 7 + 7x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + 7x + -2x = 13 + 2x + -2x Combine like terms: 7x + -2x = 5x 7 + 5x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + 5x = 13 + 0 7 + 5x = 13 Add '-7' to each side of the equation. 7 + -7 + 5x = 13 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 13 + -7 5x = 13 + -7 Combine like terms: 13 + -7 = 6 5x = 6 Divide each side by '5'. x = 1.2 Simplifying x = 1.2
| 2(x+2)+8=6 | | 6(6-3x)=-108 | | 3(2x+4)=6(x+2) | | 7n+8=3n | | 9y-8=4y*7y+16 | | -7(10+3x)=-196 | | -3x=2x+15 | | 5(5+7x)=-150 | | 5x-8=2x+1 | | x+4(x+3)=17 | | (9y^2+8y-2)-(9y^2+5)=9 | | 4x-(2x+6)=8x-12 | | -5x-7=-8-6x | | 4y+2=3*6-4y | | n-3+4n=-11 | | 2x-3(x+4)=17 | | 7x-3-x=-27 | | 5x-3=8x+6 | | -3+3x=-30 | | -5(5-x)=-20 | | Q=X-P | | 5(x+1)=3(2x+3)+5 | | -10=x+5+4x | | 4(5x-3)+4(x+1)=-3(2x+6)-2(x-1) | | 3(-5x+7)=96 | | 7(3+p)= | | 2x-18+8x+1=20+5x-2 | | 4(-7x+9)=-188 | | 8(4+m)= | | 4a+9a=39 | | 3a+9a=39 | | 3x-2(5-x)=-3(x-10)+3x |